EFFECT OF SELF- MOUNTING ON COCOON AND POST - COCOON PARAMETERS IN SILKWORM BOMBYX MORI. L. - HIMANTHARAJ, M. T.; CHOWDHURY, MEENAKSHI; VINDHYA, G. S.; RAHAMATHULLA, V.K. RAHAMATHULLA; RAJAN, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
In silkworm rearing, self-mounting is rational method of mounting to save labour and time. But in self-mounting, mounting rate is low. To improve the mounting rate various repellents viz. lime, sawdust, kaolin and management practices were tried. Lime and saw dust was found better because of maximum number of larvae climbed and formed the cocoons in the mountage (96.9% & 96.0%), minimum percentage of defective cocoons (5.15% & 5.57%) in lime and saw dust respectively. Further, there was no bad effect on cocoon and post cocoon parameters.